PO.5.103 Study of b cells in patients with lupus nephritis: parameters of disease activity and remission. (27th September 2022) - Di Mario, C; Varriano, V; Petricca, L; Paglionico, AM; Gigante, MR; Alivernini, S; Tolusso, B; Gremese, E
Abstract : Purpose: B cells play a pivotal role in systemic lupus erythematosus (SLE) pathogenesis. The aim of this study was to investigate the relationship between peripheral blood B cell phenotype, disease activity and histological lesions in lupus nephritis (LN-SLE). Methods: One hundred LN-SLE with active renal involvement, 40 at disease diagnosis (Early) and 60 in whom LN occurred after the disease diagnosis (Long) were enrolled, 37 controls were included. Clinical, laboratory and demographic data were collected at baseline and after 6 and 12 months. Disease activity was recorded using SLEDAI-2K. Nephritic class was evaluated according to the ISN/RPS classification. Memory B cells immunophenotyping (IgD/CD27 classification) was analyzed in peripheral blood through flow cytometry. IL-6 and BAFF serum levels were assayed by ELISA. Results: There were no differences in the distribution of the renal classes and in activity and chronicity indices in the Early and Long groups. A direct correlation was observed between chronicity index score and creatinine in the whole cohort (R=0.342;p<0.01) and in Early (R=0.528;p=0.01) and Long (R=0.337;p=0.02). The histological activity index was significantly higher in anti-dsDNA positive than in negative ones (6.6±4.8 vs 2.8±3.5;p=0.01), and in patients with at least one antiphospholipid (APL-ab) positivity (6.8±4.8 vs 5.1±4.8;p=0.05). The presence of histological lesions (glomerulosclerosis and fibrocellular crescents) and the positivity for at least one of the APL-ab were associated to the failure in achieving clinical remission within 12 months, while baseline 24h-UP levels ≤2750mg were associated to remission achievement [OR:2.6(95%CIs:1.1–5.8)]. Regarding B cells subsets, a lower percentage of CD19pos and IgDposCD27pos in LN-SLE compared to controls (6.8±5.5% vs 10.5±3.5%;p<0.01 and 11.1±12.0% vs 15.3±8.0%;p<0.01, respectively) was observed. In addition, we found higher levels of IgDnegCD27neg and CD27posCD38pos in LN-SLE than in controls [(CD27negIgDneg10.0±8.7% vs 4.1±1.9%;p<0.01)(CD27posCD38pos4.4±5.3% vs 1.0±0.5%;p<0.01)]. Furthermore, CD19pos and IgDposCD27pos negatively correlated with BAFF (R=-0.327;p=0.03 and R=-0.305;p=0.04 respectively), while a direct correlation was observed between IgDnegCD27neg B cells and IL-6 levels (R=0.302;p<0.01). Considering the remission status, both remission and no remission had significantly lower frequencies of IgDposCD27pos than controls [(Remission:10.7±12.4% vs 15.3±8.0%;p<0.01)(No-Remission:9.8±9.5% vs 15.3±8.0%;p<0.01)] conversely had a significantly higher rate of IgDnegCD27neg [(Remission:11.5±10.0% vs 4.1±1.9%;p<0.01;NoRemission:9.6±6.7% vs 4.1±1.9%;p<0.01] and plasmablasts [(Remission 5.2±6.7% vs 1.0±0.5;p=0.05;NoRemission:4.1±3.4 vs 1.0±0.5;p<0.01)] than controls. Conclusion: LN-SLE active injury and chronic damage histological features seemed to not depend on disease duration per se. Memory B cells immunophenotyping reveals a distinct B cells subset of LN-SLE patients when compared to healthy controls, confirming a change in the B cells subsets in SLE patients and strengthening the hypothesis of the possible role of B lymphocytes as biomarker in the course of LN.